2022
DOI: 10.1002/qre.3128
|View full text |Cite
|
Sign up to set email alerts
|

An expanded case against synthetic‐type control charts

Abstract: During the last two decades, many new methods have appeared in statistical process monitoring with synthetic‐type control charts being a prominent constituent. These charts became popular due to their simplicity and proclaimed excellent change point detection performance. Synthetic charts are nothing more than the application of well‐known and long established runs rules. We show that better performance can be obtained by using exponentially weighted moving average (EWMA) charts. Expanding on some previous que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
(154 reference statements)
0
3
0
Order By: Relevance
“…It is important to know the process components and behavior to be monitored to select the best control chart or a set of control charts to compare with. Also, it is important to identify deceiving trends in certain types of control charts recalled in the SPM literature [77], [78], [79], [80], [81] to avoid their use. If these recommendations are not followed, the number of false alarms or undetected signals could increase significantly.…”
Section: Gaps In Using Data-driven Methods Combined With a Control Chartmentioning
confidence: 99%
“…It is important to know the process components and behavior to be monitored to select the best control chart or a set of control charts to compare with. Also, it is important to identify deceiving trends in certain types of control charts recalled in the SPM literature [77], [78], [79], [80], [81] to avoid their use. If these recommendations are not followed, the number of false alarms or undetected signals could increase significantly.…”
Section: Gaps In Using Data-driven Methods Combined With a Control Chartmentioning
confidence: 99%
“…A number of researchers have argued that when the IC process distribution is unknown or unspecified, then the OOC 𝐴𝑅𝐿 metric is not a good criterion for the performance comparison of different schemes; see for instance, Kenett and Pollak 18 and Knoth. 19 In such case, they recommend the use of the CED criterion. Kenett and Pollak 18 defined the CED as "the delay from the first opportunity to detect a change and not from the time of change itself".…”
Section: The Ced Criterionmentioning
confidence: 99%
“…Davis and Woodall 100 indicated that the synthetic chart is nothing more than a particular runs‐rule chart. Moreover, Knoth 101,102 criticized the design performance of synthetic charts and showed that not only these charts do not have an advantage over the standard charts, they also cause information loss about the process data.…”
Section: Categorizing Literature Based On Type Of Control Charts Unde...mentioning
confidence: 99%